2000
DOI: 10.1007/s10434-000-0656-y
|View full text |Cite
|
Sign up to set email alerts
|

Ductal Carcinoma-In-Situ: Long-Term Results of Breast-Conserving Therapy

Abstract: DCIS is a favorable disease with an excellent long-term survival. The locoregional recurrence rate in patients with DCIS treated with BCT is similar to that in patients with early-stage invasive breast cancer treated with BCT, but time to locoregional recurrence is significantly longer in patients with DCIS. In patients with DCIS treated with BCT, intense surveillance for locoregional recurrence needs to be maintained for the patient's lifetime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Silverstein (2003) noted that DCIS is a heterogeneous group of lesions, and thus a uniform treatment policy is inappropriate, as different patients will require or benefit from different treatment options (Silverstein, 2003). In a review of 21 studies involving DCIS patients who were treated by mastectomy, a 0.4% incidence of recurrence was observed (Lagios et al, 1989;Boyages et al, 1999;Silverstein et al, 1999;Mirza et al, 2000). Significantly lower local recurrence rates after a total mastectomy compared to corresponding rates after BCS were confirmed by Cutuli et al (2001), who reported local recurrence rates of 2.1%, 30.1%, and 13.8% in the mastectomy, BCS alone, and BCS with RT patient groups, respectively, after a 91 month follow-up period (Cutuli et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Silverstein (2003) noted that DCIS is a heterogeneous group of lesions, and thus a uniform treatment policy is inappropriate, as different patients will require or benefit from different treatment options (Silverstein, 2003). In a review of 21 studies involving DCIS patients who were treated by mastectomy, a 0.4% incidence of recurrence was observed (Lagios et al, 1989;Boyages et al, 1999;Silverstein et al, 1999;Mirza et al, 2000). Significantly lower local recurrence rates after a total mastectomy compared to corresponding rates after BCS were confirmed by Cutuli et al (2001), who reported local recurrence rates of 2.1%, 30.1%, and 13.8% in the mastectomy, BCS alone, and BCS with RT patient groups, respectively, after a 91 month follow-up period (Cutuli et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…There are two currently-held concepts that meet with general agreement on this topic: the first is the evidence that wide surgical excision and negative margins of resection decrease the risk of LR in patients with mammographically-detected DIN treated with BCS and radiation [26]. The second concept is a general consensus that patients with positive margins show a significantly higher rate of LR than do patients with negative margins, regardless of irradiation or tamoxifen administration [27][28].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Particularly, the greatest potential clinical impact could be intraoperative detection of DCIS, which has a very important status in breast pathology because its presence is a powerful predictor for local disease reoccurrence and its identification during surgery influences treatment options. [51][52][53][54] DCIS is a nonpalpable lesion, unidentifiable during surgery; consequently, characterization of its spectral response could dramatically improve patient care. Finally, understanding the relationship between the optical and biological properties of a tissue will ultimately improve the diagnostic utility of optical techniques, permitting optimization of the measurement procedure and signal analysis for enhanced sensitivity to differentiating features.…”
Section: Discussionmentioning
confidence: 99%